Newly detected shock-induced high-pressure phases formed in amphibolite clasts of the suevite breccia (Ries impact crater, Germany): liebermannite, kokchetavite, and other ultrahigh-pressure phases - Stähle, Volker; Chanmuang Nasdala, Chutimun; Schwarz, Winfried H.; Trieloff, Mario; Varychev, Alexander (Contributions to mineralogy and petrology, 2022)
Amphibolite clasts in the suevite of the Ries impact crater contain shock-induced melt veins (SMVs) with high-pressure phases such as majoritic garnet, jadeitic clinopyroxene and others. In addition, heat conduction from hot SMVs into adjacent rock portions locally produced further high P-T melt pools. These melts were preferentially generated in rock domains, where the SMVs cross older (‘pre-Ries’) veinlets with analcime or prehnite and larger grains of sericitized plagioclase. Melting of such chemically different local bulk systems (Na-, Ca-, Ca-Na- and K-Na-rich) was facilitated by low solidus temperatures of the original secondary OH-bearing phases. From the resulting shock-induced melts, liebermannite, kokchetavite, jadeite, nonstoichiometric and albitic jadeite, grossular, vuagnatite, lawsonite + coesite, and clinozoisite crystallized during pressure release. Vuagnatite is now proven to be a genuine high-pressure phase. Its ubiquitous distance of 20-35 μm from the hot shock veins suggests a temperature sensitivity typical for an OH-bearing phase. In local Na-rich melts albitic jadeite appears instead of the assemblage jadeite + SiO2. Liebermannite, a dense polymorph of K-feldspar was identified by Raman spectroscopy. After stishovite, liebermannite constitutes the second known high-pressure phase in the Ries that contains silicon exclusively in six-fold coordination. The KAlSi3O8-polymorph kokchetavite was formed in alkali-rich melt glasses. Pressure and temperature values in the range of about 8-11 GPa and ~ 800-1100 °C were estimated from the chemical compositions of locally occurring majoritic garnets (Si = 3.21-3.32 and 3.06-3.10 apfu), respectively, and the presence of fine-grained aggregates of lawsonite and coesite. Generally, the neighboring areas of the veins are characterized by a sequence of variable high-pressure phases documenting strongly falling P-T conditions with increasing distance from the vein. These novel features enlighten the dynamic event during passage of a shock wave.
Gesehen am 31.10.2022